2019
DOI: 10.1097/prs.0000000000005502
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Preferred Incision Location for Nipple-Sparing Mastectomy? A Systematic Review and Meta-Analysis

Abstract: Background: The incidence of nipple-sparing mastectomy is rising, but no single incision type has been proven to be superior. This study systematically evaluated the rate and efficacy of various nipple-sparing mastectomy incision locations, focusing on nipple-areola complex necrosis and reconstructive method. Methods: A systematic literature review was performed according to the Preferred Reporting Items for Systematic Review and Meta-Analyses guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 51 publications
1
82
0
Order By: Relevance
“…When considering how to implement the conclusions described by the authors, the practicing plastic surgeon must contextualize the surgical plan with the individual patient’s oncologic needs, treatment plan, general state of health, breast size and shape, body mass index, and the patient’s preference and priorities. 13 , 14 Obstacles to executing the ideal breast reconstruction will inevitably arise and the surgical plan must be modified to preserve the patient’s health and promote uneventful healing as the primary directives.…”
Section: Discussionmentioning
confidence: 99%
“…When considering how to implement the conclusions described by the authors, the practicing plastic surgeon must contextualize the surgical plan with the individual patient’s oncologic needs, treatment plan, general state of health, breast size and shape, body mass index, and the patient’s preference and priorities. 13 , 14 Obstacles to executing the ideal breast reconstruction will inevitably arise and the surgical plan must be modified to preserve the patient’s health and promote uneventful healing as the primary directives.…”
Section: Discussionmentioning
confidence: 99%
“…NAC necrosis is considered the most problematic complication of NSM, leading to adverse outcomes such as nipple deformity, hypopigmentation in the NAC area, or loss of the NAC. The rate of NAC ischemia or necrosis after NSM ranges from 0% to 48%, with large variations across different studies [ 2 , 5 , 8 , [19] , [20] , [21] , [22] ]. However, a meta-analysis of recent studies revealed an overall partial NAC necrosis rate of 4.62% and a complete NAC necrosis rate of 2.49%, which are acceptably low [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of NAC ischemia or necrosis after NSM ranges from 0% to 48%, with large variations across different studies [ 2 , 5 , 8 , [19] , [20] , [21] , [22] ]. However, a meta-analysis of recent studies revealed an overall partial NAC necrosis rate of 4.62% and a complete NAC necrosis rate of 2.49%, which are acceptably low [ 22 ]. Several studies have identified the type of surgical incision as one of the risk factors of NAC necrosis, with the highest necrosis rate in periareolar incision [ 8 , 19 , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 While many different types of incisions have been used in NSM, the inframammary incision is associated with lower rates of complications, including nipple necrosis. 8 , 9…”
Section: Goals Of the Proceduresmentioning
confidence: 99%